2015
DOI: 10.1515/joc-2014-0091
|View full text |Cite
|
Sign up to set email alerts
|

5 × 5 25 Gbit/s WDM-MDM

Abstract: Wavelength-division multiplexed-passive optical network (WDM-PON) is a revolutionary high-capacity and scalable broadband access network. This paper capitalizes on Laguerre-Gaussian (LG) modes to reduce modal dispersion and increase data capacity. A data rate of 25 Gbit/s is attained for a multimode fiber link by multiplexing five LG modes on five wavelengths centered at 1,550.12 nm for a distance up to 800 m.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…MDM has been realized through through holographic wavefront generation [9][10][11][12], multi-core fibers [13][14][15], mode-selective fiber couplers [16][17][18], laser cavity design [19][20][21] or via optical signal processing [17,22,23].…”
Section: Related Workmentioning
confidence: 99%
“…MDM has been realized through through holographic wavefront generation [9][10][11][12], multi-core fibers [13][14][15], mode-selective fiber couplers [16][17][18], laser cavity design [19][20][21] or via optical signal processing [17,22,23].…”
Section: Related Workmentioning
confidence: 99%
“…Z. Zhao et al reported an ultrahigh capacity FSO communication system over strong atmospheric turbulence conditions by incorporating hybridization of OAM multiplexing, polarization multiplexing, and frequency multiplexing [39]. The research works in references [40][41][42][43][44] report the simulative analysis of MDM-based high-capacity radio over fiber (RoF) links.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the FSO guarantees increasing the capacity by using mode division multiplexing (MDM) technology. MDM is a promising technology [9][10][11] used to transmit the optical signal or light beams in form of modes such as Laguerre-Gaussian mode [12,13], Hermite-Gaussian (HG) mode [14,15], helical-phase mode [16,1718], spot mode, and donut mode [14,16,19] through the transmission channel that leads to expand the capacity . This technology has been used over optical fibre and FSO, where it successfully achieved increasing the data capacity.…”
Section: Introductionmentioning
confidence: 99%